The Socioeconomic Impacts of Energy Reform in Tunisia : A Simulation Approach - Cuesta, José; El-Lahga, Abdel Rahmen; Lara Ibarra, Gabriel (World Bank, Washington, DC, 2015)
Tunisian social development policy making has always counted on energy subsidies to play a pivotal role. Due to the increasingly unsustainable budget implications, a new strategy has begun to reform the subsidy system in the energy sector while striking a balance between improving fiscal and equity considerations without increasing social tensions. This paper presents an analysis of the fiscal and distributive consequences of the changes to the subsidy setup announced by the government at the end of 2014. The results show that raising electricity prices for consumers and removing subsidies for other energy sources would lead to a short-term increase in the poverty rate of 2.5 percentage points. In addition, compensation mechanisms that could be readily implemented (such as universal coverage or building on the existing health cards system) will not bring substantive counterweight to the increased poverty, even if all savings of reforms could be perfectly channeled as cash transfers. The analysis suggests that bold reforms of energy subsidies need to be accompanied by equally bold improvements to the targeting schemes of public spending if poverty and disparities are to be substantively reduced.